Prediction of mutant activity and its application in molecular design of tumor necrosis factor-a - 唐卫东 奚涛 王波 郭冬林 徐贤秀 朱德煦 (Science China. Life sciences, 1997)
Two models for prediction of the activity and stability of site-directed mutagenesis on tumor necrosis factor-α are established. The models are based on straightforward structural considerations, which do not require the elaboration of site-directed mutagenesis on the protein core and the hydrophobic surface area by analyzing the properties of the mutated amino acid residues. The reliabilities of the models have been tested by analyzing the mutants of tumor necrosis factor-α (TNF-α) whose two leucine residues (L29, L157) were mutated. Based on these models, a TNF-α mutant with high activity was created by molecular design.